Comparative characteristics of elite New Zealand and South African u/16 rugby-players with reference to game-specific skills, physical abilities and anthropometric data - Kruger, P.E. (Pieter Ernst) (University of Pretoria, 2013)
Dissertation (MA (Human Movement Sciences))--University of Pretoria, 2008.